CREB/TRH pathway in the central nervous system regulates energy expenditure in response to deprivation of an essential amino acid - Xia, T; Zhang, Q; Xiao, Y; Wang, C; Yu, J; Liu, H; Liu, B; Zhang, Y; Chen, S; Liu, Y; Chen, Y; Guo, F (International Journal of Obesity, 2015)
Background: In the central nervous system (CNS), thyrotropin-releasing hormone (TRH) has an important role in regulating energy balance. We previously showed that dietary deprivation of leucine in mice increases energy expenditure through CNS-dependent regulation. However, the involvement of central TRH in this regulation has not been reported. Methods: Male C57J/B6 mice were maintained on a control or leucine-deficient diet for 7 days. Leucine-deprived mice were either third intracerebroventricular (i.c.v.) injected with a TRH antibody followed by intraperitoneal (i.p.) injection of triiodothyronine (T3) or i.c.v. administrated with an adenovirus of shCREB (cAMP-response element binding protein) followed by i.c.v. injection of TRH. Food intake and body weight were monitored daily. Oxygen consumption, physical activity and rectal temperature were assessed after the treatment. After being killed, the hypothalamus and the brown adipose tissue were collected and the expression of related genes and proteins related was analyzed. In other experiments, control or leucine-deficient medium incubated primary cultured neurons were either infected with adenovirus-mediated short hairpin RNA targeting extracellular signal-regulated kinases 1 and 2 (Ad-shERK1/2) or transfected with plasmid-overexpressing protein phosphatase 1 regulatory subunit 3C (PPP1R3C). Results: I.c.v. administration of anti-TRH antibodies significantly reduced leucine deprivation-stimulated energy expenditure. Furthermore, the effects of i.c.v. TRH antibodies were reversed by i.p. injection of T3 during leucine deprivation. Moreover, i.c.v. injection of Ad-shCREB (adenovirus-mediated short hairpin RNA targeting CREB) significantly suppressed leucine deprivation-stimulated energy expenditure via modulation of TRH expression. Lastly, TRH expression was regulated by CREB, which was phosphorylated by ERK1/2 and dephosphorylated by PPP1R3C-containing protein Ser/Thr phosphatase type 1 (PP1) under leucine deprivation in vitro. Conclusions: Our data indicate a novel role for TRH in regulating energy expenditure via T3 during leucine deprivation. Furthermore, our findings reveal that TRH expression is activated by CREB, which is phosphorylated by ERK1/2 and dephosphorylated by PPP1R3C-containing PP1. Collectively, our studies provide novel insights into the regulation of energy homeostasis by the CNS in response to an essential amino-acid deprivation.